Yolk-shell structured magnetic mesoporous organosilica supported ionic liquid/Cu complex: an efficient nanocatalyst for the green synthesis of pyranopyrazoles - Neysi, Maryam; Elhamifar, Dawood (Frontiers in Chemistry, 2023)
In the present study, a novel magnetic methylene-based periodic mesoporous organosilica (PMO) supported ionic liquid/Cu complex with yolk-shell structure (YS-Fe3O4@PMO/IL-Cu) is prepared via the soft template-assisted method. The TGA, FT-IR, SEM, EDX, XRD, VSM, nitrogen-sorption, and ICP techniques were employed to identify YS-Fe3O4@PMO/IL-Cu. The YS-Fe3O4@PMO/IL-Cu material was applied as a powerful nanocatalyst for the synthesis of pyranopyrazoles under ultrasonic media. The study demonstrated that the YS-Fe3O4@PMO/IL-Cu nanocatalyst is highly recyclable, selective, and effective. The leaching test was performed to study the nature of the designed catalyst under applied conditions.